LEVEL OF ADOPTION OF CATTLE FARMERS TO THE USING OF BIOGAS IN BONE REGENCY,SOUTH SULAWESI PROVINCE - Sitti Nurani Sirajuddin; Muhammad Irfan Said; Muhammad Zain Mide (Jurnal Ilmu dan Industri Peternakan, 2014)
ABSTRACT. The aim of this research was to know the level of adoption of cattle farmers to the use of biogas in Bone Regency,South Sulawesi Province. This research was conducted for two month started from April 2013 until May 2013 in Libureng Disctrict, Bone Regency. Population covered all cattle farmers, while sample of this research were member of farmers groups namaley Lakeppang and Turu Adae who name been trained about how to make biogas. The research revealed that the level of adoption of cattle farmers to the using of biogas was stilllows so farmers need more intensif extention and using biogas.